(untitled) (The International Journal for Scientific Research, 2024)
This study aims to identify the extent of the impact of stealth marketing in its dimensions (viral marketing, deceptive marketing, brand advocates, celebrity endorsements) through its modern techniques on the development of customer commitment in its dimensions (emotional, continuance, normative) with an application to Almarai customers in Saudi Arabia. The study followed a descriptive approach using the survey method. Among the most important results of the study was the acceptance of the first hypothesis, which states that there is a statistically significant effect at a significance level of (0.05) of stealth marketing in its dimensions on the emotional commitment of Almarai customers in Saudi Arabia. The second hypothesis was also accepted, stating that there is a statistically significant effect at a significance level of (0.05) of stealth marketing in its dimensions on the continuance commitment of Almarai customers in Saudi Arabia. Additionally, the third hypothesis was accepted, indicating a statistically significant effect at a significance level of (0.05) of stealth marketing in its dimensions on the normative commitment of Almarai customers in Saudi Arabia. The study recommended directing the marketing efforts of companies to benefit from the advantages of each technique of stealth marketing and to avoid the drawbacks of these techniques in a way that contributes to achieving the marketing goals of companies. It is also necessary to enhance the positive aspects that stealth marketing includes by avoiding deception and exaggeration in presenting the advertising message through companies using over-the-top marketing techniques. Furthermore, it is essential to consider the ethical aspects, customs, and traditions of our societies that may not align with some of these techniques, as well as to determine which are more effective in achieving marketing activity goals. The design of the advertising message and the selection of the appropriate technique for presenting it should consider the cultural levels of the targeted customers and the level of marketing awareness that the customer has reached. This can be achieved through proactive measures to determine this, in addition to identifying customer preferences and desires.